EFEKTIVITAS PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI, DAN PERILAKU TIDAK ETIS TERHADAP KECURANGAN AKUNTANSI - Marsel Joi Damarjanan; Trisna Sari Lewaru; Paskanova Christi Gainau (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2025)
Purpose: to determine the effectiveness of internal control, compliance with accounting rules, and unethical behavior on accounting fraud at RSUD Dr. M. Haulussy Ambon. Methodology/approach: This research uses a quantitative method with questionnaires as the primary source of data. The population in this study is all department heads at RSUD Dr. M. Haulussy Ambon. The purposive sampling technique is used to select samples with specific criteria, namely employees in the Finance and Fund Mobilization Department, the Sub-Verification and Accounting Department, and the Public Relations Officer, with a total of 38 respondents. The data analysis method used in this study is multiple linear regression analysis using SPSS 26. Findings: The results of this study indicate that the effectiveness of internal control and unethical behavior do not influence accounting fraud at RSUD Dr. M. Haulussy Ambon. However, compliance with accounting rules influences accounting fraud. Practical implications: Originality/value: RSUD Dr. Haulussy Ambon can focus more on their internal control to improve the awareness regarding obedience to the accounting regulation. Additionally, the hospital should give the punishment for the employee who made the unethical action.